Ultrasonic studies on inorganic fertilizers - , A.Gomathiyalini, S.Rathika, K.Renuka Devi*, S.Geetha, (International Journal of Scientific Research and Management (IJSRM), 2016)
In the present study, the ultrasonic velocity of aqueous solutions of ammonium sulphate and diammonium phosphatefertilizers has been measured in the concentration range of 0.1m to 0.6m at 303◦K. The variation of ultrasonic velocity is notlinear and the non-linearity of this is confirmed by adiabatic compressibility study also. The study was also extended toaqueous solution of diammonium phosphate in 0.3m ammonium sulphate to study the influence of ammonium sulphate on thenature of molecular interactions. Using the measured values of ultrasonic velocity, density, viscosity, acoustic parameters likeadiabatic compressibility, intermolecular free length, acoustic impedance, relaxation time, free volume, internal pressure andsolvation number have been evaluated. These parameters are used to discuss the molecular interactions of these compoundswith water molecules